Clinical management of drug-resistant tuberculosis in resource constrained settings - Palmero, Domingo (2013)
Drug-resistant forms of tuberculosis (TB), particularly multi- and extensively drug-resistant TB, represent an important obstacle to global control of the disease. Recently, new drugs, repurposed drugs, and new drug combinations have been evaluated, with a number showing promise for the treatment of drug-resistant TB. Additionally, a range of methods for accelerating mycobacterial culture, identification, and drug susceptibility testing have been developed, and several in-house and commercial genotyping methods for speeding drug resistance detection have become available. Despite these significant achievements in drug development and diagnostics, drug-resistant TB continues to be difficult to diagnose and treat. Significant international efforts are still needed, especially in the field of clinical and operational research, to translate these encouraging developments into effective patient cure and make them readily available to resource-constrained settings, where they are most needed.